ANALYSIS OF STIFFNESS RESEARCH OF REINFORCED COMPOSITES IN RADIO ENGINEERING AND MEDICINE - MOSIY, LYUBOMYR; SVERSTYUK, ANDRIY; REMEZ, ANDRIY; MARKOVSKYI, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents a comprehensive study of reinforced composite materials for reflective arrays and biomedical applications, combining bibliometric analysis of scientific trends and mathematical modeling of stress-strain states in antenna structures. Based on analysis of 652 publications in Scopus database over 10-year period, stable growth in research activity was revealed with peak in 2024 (114 publications). Geographic distribution demonstrates leadership of China (32.5%) and USA (21.1%). The applied bibliometric approach confirmed universality of statistical methods for interdisciplinary research. Mathematical model of temperature impact on parabolic shell of antenna mirror was developed considering anisotropic properties of composite materials. Comparative material analysis showed optimality of copper for maximum reflection efficiency, aluminum for lightweight constructions, CNT and GPL composites for structurally optimized solutions. High potential of composite materials with carbon nanotubes and graphene platelets for creating biomedical electrodes with enhanced signal-to-noise ratio (up to 40 dB) for electrocardiographic monitoring was identified. Electric arc spraying was identified as most promising technology. Numerical modeling results confirmed critical influence of temperature gradients on geometric stability of reflective surfaces. The research revealed synergistic potential between technologies for manufacturing antenna arrays and biomedical electrodes, opening prospects for developing multifunctional composite systems. The research creates scientific-methodological foundation for developing thermostable antenna systems in aerospace, energy and medical industries.
Keywords: reflective arrays; reinforced composite materials; bibliometric analysis; stress-strain state; temperature loading; electric arc spraying; carbon nanotubes; antenna systems; thermal stability; mathematical modeling; biomedical electrodes; electrocardiography; graphene composites